None of Your Business: Protecting the Right to Write Anonymous Business Reviews Online - Cherner, Lindsey (The Columbia Journal of Law & the Arts, 2017)
This Note analyzes the fine balance between First Amendment protection afforded to anonymous online business reviews and the state’s interest in removing false communications made about a business or business owner. Part I traces the development of anonymity as a protected First Amendment right and will also explain the rise of Internet speech and the protections of Section 230 of the Communications Decency Act for ISPs like Yelp and TripAdvisor. Part II illustrates the inconsistent application of three conflicting standards used for unmasking anonymous speakers on the Internet and will interpret cases that address these concerns in the context of online business reviews. This section will also touch on the significance of the unanimous passage of the Consumer Review Fairness Act of 2016 and what its enactment into law means for the future of online business reviews. Finally, this section will distinguish commercial speech from non-commercial speech and explain why the distinction is relevant to the level of protection afforded to online business reviews. In Part III, this Note argues that upon receiving a motion to quash from an anonymous business reviewer, courts should incorporate a totality of the circumstances analysis in addition to balancing the interests of the First Amendment with the right to redress against defamatory harms. This section also argues that first-hand opinions about business experiences and commercial goods and services are usually not commercial speech; and therefore, should receive more protection than traditional commercial speech. In Part IV, this Note concludes by explaining that considerations of the type of speech, the forum used, and the context in which it is posted online should guide the courts’ analysis prior to the decision to unmask the author of an anonymous online business review. As part of this totality of the circumstances analysis, courts should keep in mind that forums that do not employ fact-checking protections should not face the same heightened liability as those that do fact-check online communications. Affording less liability to ISPs like Yelp and TripAdvisor than newspapers with extensive layers of editorial support makes sense long-term because consumers have become savvier at determining the reliability of business reviews and are more keen at sifting through the helpful and unhelpful reviews on their own. With this in mind, it would be more beneficial to allow all candid opinions to enter the proverbial marketplace of ideas with the ultimate determination of reliability in the hands of those at their keyboards rather than the businessmen and women who have been criticized. As this Note illustrates, we need anonymous business reviews, for without them, there may be trepidation that businesses will take advantage of consumers’ naïve hearts and minds.